Escritório de projetos de pesquisa - Telles, Maria Hortência da Costa; da Costa, Sttela Regina Reis (Revista Gestão da Produção Operações e Sistemas, 2007)
The management of projects financed by fostering agencies is one of the greatest challenges faced by the researchinstitutions. This paper presents a proposal made by the Project Operations Group of the National Institute ofMetrology, Standardization and Industrial Quality (Inmetro) for this type of management. This Group will bea type of combination of a project office with the Project Support Office and the Project Management Center ofExcellence. The proposal was elaborated after the evaluation of the data obtained in the operational flow surveyof the project-related activities, interviews with project coordinators and employees from several Inmetro’sOperating Units. It is intended to assure that the project management be efficaciously performed, thus promotingresults from the developed projects, influencing the industry and the citizen’s quality of life. However, theimplementation of a project office such as the Project Operating Group will mean the insertion of institutionalchanges, usually difficult to be accepted. It is fundamental for the success of GPROD to understand that everyoneinvolved in the processes are partners, and that it will offer services and solutions to the problems found,according to the Inmetro structure.Keywords: Research project; Project office; Operating project management; Fostering agencies.